Effect of Hulless Barley Flours on Dough Rheological Properties, Baking Quality, and Starch Digestibility of Wheat Bread - Yu, Liwei; Ma, Yanrong; Zhao, Yiyue; Pan, Yilin; Tian, Renmei; Yao, Xiaohua; Yao, Youhua; Cao, Xinyou; Geng, La; Wang, Zhonghua; Wu, Kunlun; Gao, Xin (Frontiers in Nutrition, 2021)
Hulless barley (Hordeum vulgare L.), also known as highland barley, contains nutritional compounds, such as β-glucan and polyphenol, which can be added to wheat flour to improve the dough nutritional quality. In this study, differently formulated dough samples were obtained by individually adding four hulless barley flours into flour of a wheat variety (Jimai 44) which has very strong gluten. The effects of hulless barley supplementation on gluten structure, dough rheological properties, bread-making properties and starch digestibility were assessed. The results showed that compared with Jimai 44 dough, substitution of hulless barley flour to wheat flour at levels ranging from 10% to 40% negatively affected gluten micro-structure and dough mixing behavior, because the cross-links of gluten network were partially broken and the dough development time and stability time were shortened. For the hulless barley-supplemented bread, specific volume was significantly increased while springiness was not greatly changed. Furthermore, the trend of hydrolysed starch in hulless barley-supplemented bread was significantly reduced along with the increase of digestion time, compared with wheat bread. Importantly, the contents of β-glucan, polyphenols and flavonoids in hulless barley-supplemented bread were 132.61%-160.87%, 5.71%-48.57% and 25%-293.75% higher than those in JM bread, respectively. Taken together, the hulless barley-supplemented bread has been fortified with enhanced nutritional components, more desirable bread-making quality, and improved starch hydrolytic properties, which shows a great potential to use hulless barley as a health supplement.